Building a One Health mobile laboratory workforce: strengthening public health preparedness across Europe and Africa - Aryse Martins Melo; Beate Becker-Ziaja; Markus Keller; Duncan Sangale; Dewi Ismajani Puradiredja; Theresa Habermann; Juliane Bönecke; Alexandru Tomazatos; Johannes R. Peham; Birgit Michalek; Andry Aasamäe; Georg G. Duscher; et al. (Human Resources for Health, 2026)
Abstract The emergence and re-emergence of infectious diseases remain a major public health threat in Europe. The Horizon Europe-funded MOBILISE project addresses this challenge by establishing a One Health Mobile Laboratory capable of handling risk group 3 and 4 pathogens, while strengthening outbreak preparedness through targeted capacity-building activities and the development of a rapid-response expert network. A key component of the project is a training-of-trainers (ToT) model, which enables participants to perform critical tasks in the field and transfer expertise within their home countries. This approach expands the pool of skilled professionals and strengthens collective preparedness. A descriptive mixed-methods programme evaluation, including pre- and post-test assessments, was conducted to assess the ToT model's implementation. In the first phase, two laboratory experts from each partner country were selected. They completed online courses, followed by a two-week in-person training at the Bernhard Nocht Institute for Tropical Medicine in Hamburg, Germany. Training covered biosafety, molecular diagnostics, sequencing, and mobile laboratory operation. The programme concluded with four field missions, allowing participants to apply their skills and train new cohorts. The evaluation also highlighted challenges related to retaining trained experts within the expert pool over time. This structured approach enhances outbreak preparedness, fosters cross-border collaboration, and strengthens the resilience of the health system.